Effect of Prebiotic Yeast Cell Wall on Starter Broilers Undergoing Gastrointestinal Challenge - Abdaljaleei, Raghad Ali; Alsadwi, AM; Al-Ajeeli , M; Leyva-Jimenez , H; Byrd, JA; Bailey, CA (The Iraqi Journal of Veterinary Medicine, 2026)
In recent years, yeast cell wall (YCW) prebiotics have been increasingly explored as alternatives to prophylactic antibiotic growth promoters in poultry production. Threonine, the third limiting amino acid in broiler diets, plays an essential role in protein synthesis and gut health. This study evaluated the effects of dietary YCW supplementation on ileal amino acid digestibility, intestinal morphology, and performance of starter broilers fed a marginal threonine-to-lysine ratio (0.60) under gastrointestinal challenge conditions. A total of 240 one-day-old Ross 308 broiler chicks were used in a 21-day experiment. Birds were allocated to 48 pens, with 5 birds per pen, and assigned to four dietary treatments. A basal diet containing 22% crude protein, 2980 kcal/kg metabolizable energy, 1.35% calculated lysine, and 0.81% calculated threonine was prepared and supplemented with or without YCW at 250 ppm. To induce a gastrointestinal immune challenge, birds were vaccinated at 10 days of age with a commercial infectious bursal disease vaccine at 10 times the recommended dose, followed by oral challenge with Clostridium perfringens on days 16 and 17. Growth performance was assessed on days 10, 16, and 21. On day 21, ileal digesta were collected for amino acid digestibility analysis, and jejunal and ileal tissues were sampled for histomorphological measurements. Supplementation with 250 ppm YCW significantly improved body weight gain, feed conversion ratio, and productivity index before challenge and after infectious bursal disease vaccination. After C. perfringens challenge, a significant interaction was observed for productivity index, with the highest value recorded in non-challenged birds receiving YCW. Overall, YCW supplementation improved the productivity index of broilers fed a low threonine-to-lysine ratio, mainly through reduced mortality. However, it did not significantly influence ileal amino acid digestibility, intestinal morphology, or necrotic enteritis lesion scores.